Co-construcción de Soluciones barriales participativas caso de estudio Barrio “Daniel Álvarez” de la ciudad de Loja. - Guachón Lanche, Christian Fabian (2023)
The present investigation is part of the project of linking the Public Administration career. The same one that supports effective solutions, applying participatory, independent and democratic processes, aimed at meeting citizen demands according to the reality of their problems, it is an action-research, exploitative and descriptive, the main results are: To the first objective, it was possible to promote neighborhood participation and organization through a meeting with the board of directors, to publicize the project of linking Co-construction of neighborhood solutions in order to reactivate the board by proposing improvement strategies and the empowerment of residents to greater participation; second objective, a diagnosis of community needs was built, with the use of some instruments such as direct observation of all neighborhood sectors and it was possible to observe with greater shortcomings in sectors 2 and 3 that there was no road maintenance and lack of lighting On public roads, surveys of all households found that their infrastructure is unimportant, with 24% indicating that they were unaware of the situation because they have not been taken into account by the authorities, and interviews with key development actors , which affirmed that in sector 2 there are no major problems, which were prioritized through a matrix of seriousness and urgency, the most prominent problems, which are the streets in poor condition, the lack of road signs and poor lighting in the neighborhood, identifying through a participatory workshop the causes that produce these adverse situations and the effects for the inhabitants; The third objective was to support the design of solutions to address certain problems through the development of an action plan, which is considered a fundamental tool to address the problems that affect the community and improve the quality of life of its inhabitants. The aforementioned plan allows establishing clear and precise objectives, as well as the strategies and activities necessary to achieve them.